# How to prove that $\sum_{k=0}^n{(-1)^k{4n-2k\choose 2n}{2n\choose k}}=2^{2n}$?

$$\sum_{k=0}^n{\left( -1 \right) ^k\left( \begin{array}{c} 4n-2k\\ 2n\\\end{array} \right) \left( \begin{array}{c} 2n\\ k\\\end{array} \right)}=2^{2n}$$

I know the correctness of this formula, but how can I prove it?

Prove that$$\sum_{k=0}^n{\left( -1 \right) ^k\left( \begin{array}{c} 4n-2k\\ 2n\\\end{array} \right) \left( \begin{array}{c} 2n\\ k\\\end{array} \right)}=2^{2n}$$
Consider the following binomial expansion \begin{align*} (x^2-1)^{2n}&=\sum_{k=0}^{2n}(-1)^kx^{4n-2k}{2n\choose k} \end{align*} Put $$x=1$$ after differentiating both sides $$2n$$ times with respect to $$x$$ and you are done! (Stop reading and try it yourself for a "confidence-booster") \begin{align*} 2x(2n)(x^2-1)^{2n-1}&=\sum_k(-1)^k(4n-2k)x^{4n-2k-1}{2n\choose k}\\ 2(2n)(x^2-1)^{2n-1}+4x^2(2n)(2n-1)(x^2-1)^{2n-2}&=\sum_{k}(-1)^k(4n-2k)x^{4n-2k-1}{2n\choose k}\\ \end{align*} Let's neglect terms like the leftmost one in the above expression, for we are eventually going to put $$x=1$$ and since $$2n-k>2n-k-1$$. So, \begin{align*} \cdots+2^2x^2(2n)(2n-1)(x^2-1)^{2n-2}&=\sum_k(-1)^k(4n-2k)x^{4n-2k-1}{2n\choose k}\\ \cdots+2^3x^3(2n)(2n-1)(2n-2)(x^2-1)^{2n-3}&=\sum_k(-1)^k(4n-2k)(4n-2k-1)x^{4n-2k-2}{2n\choose k}\\ \end{align*} and so on so that at last \begin{align*} 2^{2n}x^{2n}(2n)!(x^2-1)^0&=\sum_k(-1)^k(4n-2k)(4n-2k-1)\cdots(2n-2k+1)x^{2n-2k}{2n\choose k}\\ \end{align*} Now, what is the greatest value $$k$$ can take so that the latter terms aren't zero due to differentiation $$\rightarrow2n-2k=0\Rightarrow k=n$$. So, after putting $$x=1$$, we get \begin{align*} 2^{2n}(2n)!&=\sum_{k=0}^{n}(-1)^k(4n-2k)(4n-2k-1)\cdots(2n-2k+1){2n\choose k}\\ 2^{2n}&=\sum_{k=0}^n{\left( -1 \right) ^k\left( \begin{array}{c} 4n-2k\\ 2n\\\end{array} \right) \left( \begin{array}{c} 2n\\ k\\\end{array} \right)} \end{align*}
Using the binomial series $$\sum_{k=0}^\infty\binom{2n+k}{2n}z^k=(1-z)^{-2n-1}$$, we have $$f(z):=\sum_{k=0}^\infty\binom{2n+2k}{2n}z^{2k}=\frac12\big((1-z)^{-2n-1}+(1+z)^{-2n-1}\big),$$ so that $$\binom{4n-2k}{2n}=[z^{2n-2k}]f(z)$$ using the "coefficient-of" notation.
Since $$(-1)^k\binom{2n}{k}=[z^{2k}](1-z^2)^{2n}$$, we can see a coefficient of a product: \begin{align*} \sum_{k=0}^n(-1)^k\binom{2n}{k}\binom{4n-2k}{2n}&=[z^{2n}]\big((1-z^2)^{2n}f(z)\big) \\&=\frac12[z^{2n}]\left(\frac{(1+z)^{2n}}{1-z}+\frac{(1-z)^{2n}}{1+z}\right) \\&=[z^{2n}]\frac{(1+z)^{2n}}{1-z}\qquad\color{gray}{\text{[symmetry]}} \\&=[z^{2n}]\left(\frac{(1+z)^{2n}-2^{2n}}{1-z}+\frac{2^{2n}}{1-z}\right)=2^{2n}, \end{align*} because the last parenthesized expression is the sum of a polynomial of degree $$2n-1$$ (which then doesn't contribute to the coefficient of $$z^{2n}$$) and an ordinary geometric series $$2^{2n}\sum_{k=0}^{\infty}z^k$$.
We seek to show that $$\sum_{k=0}^n (-1)^k {4n-2k\choose 2n} {2n\choose k} = 2^{2n}.$$ The LHS is $$\sum_{k=0}^n (-1)^k {4n-2k\choose 2n-2k} {2n\choose k} \\ = [z^{2n}] (1+z)^{4n} \sum_{k=0}^n (-1)^k z^{2k} (1+z)^{-2k} {2n\choose k}.$$
The coefficient extractor enforces the range ($$[z^{2n}] z^{2k} (1+z)^{4n-2k}= 0$$ when $$k\gt n$$ because $$z^{2k} (1+z)^{4n-2k} = z^{2k}+\cdots$$) and we get $$[z^{2n}] (1+z)^{4n} \sum_{k\ge 0} (-1)^k z^{2k} (1+z)^{-2k} {2n\choose k} \\ = [z^{2n}] (1+z)^{4n} \left(1-\frac{z^2}{(1+z)^2}\right)^{2n} = [z^{2n}] (1+2z)^{2n} = 2^{2n}.$$